2012
DOI: 10.1159/000341510
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV Inhibitor Improves Insulin Resistance and Steatosis in a Refractory Nonalcoholic Fatty Liver Disease Patient: A Case Report

Abstract: A 67-year-old Asian woman was referred to Kurume University Hospital due to abnormal liver function tests. She was diagnosed with nonalcoholic fatty liver disease (NAFLD). NAFLD was treated by diet therapy with medication of metformin and pioglitazone; however, NAFLD did not improve. Subsequently, the patient was administered sitagliptin. Although her energy intake and physical activity did not change, her hemoglobin A1c level was decreased from 7.8 to 6.4% 3 months after treatment. Moreover, her serum insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 36 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…The efficacy of sitagliptin therapy has been shown in patients with T2DM complicated by NAFLD [27][28][29][30] , NASH [31] or CLD caused by hepatitis C virus [32] . However, one report suggested that NAFLD may adversely affect the glycaemic control obtained with sitagliptin [33] .…”
Section: Hepatic Safetymentioning
confidence: 99%
“…The efficacy of sitagliptin therapy has been shown in patients with T2DM complicated by NAFLD [27][28][29][30] , NASH [31] or CLD caused by hepatitis C virus [32] . However, one report suggested that NAFLD may adversely affect the glycaemic control obtained with sitagliptin [33] .…”
Section: Hepatic Safetymentioning
confidence: 99%
“…This hypothesis may be supported by some previous observations. Sitagliptin reduced hepatic steatosis [32,33], which is closely linked to epicardial fat, as recently reported [34]. Furthermore, GLP-1 receptor expression in adipose tissue has been established [35] and agonists of this receptor have recently been shown to induce short term, noticeable, and significant EAT thickness reduction in type 2 diabetes patients [36], suggesting that a prolonged halflife of GLP-1 mediated by the inhibition of DPP-4 bears an important influence on the adipose reduction of this tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of sitagliptin therapy has been shown in patients with diabetes complicated by NAFLD [76][77][78], NASH [79] or CLD caused by hepatitis C virus [80].…”
Section: Sitagliptinmentioning
confidence: 99%